Capacitating stakeholders to using Climate Information in West Africa: Achievements and lessons learned from the WAAPP-funded CaSCIERA-TA project - Bayala, Jules; Dayamba, Djibril S; Lamien, Niéyidouba; Zougmoré, Robert B.; Agali, Alhassane; Ky-Dembélé, Catherine; Diakité, Adama; Ouédraogo, Mathieu; Gnangle, Cesaire; Keita, Amara; Tougiani, Abasse; Sadate, Amadou (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This Info note summarizes the achievements and lessons learned from the implementation of a 2-year project on ‘’Capacitating Stakeholders in Using Climate Information for Enhanced Resilience in the Agricultural Sector in West Africa (CaSCIERA-TA)’’, funded by Conseil Ouest et Centre Africain pour la Recherche et le Développement Agricole (CORAF) under the West Africa Agricultural Productivity Program (WAAPP)”. This project was implemented by a consortium of partners led by ICRAF Sahel Office and included CCAFS West Africa Program, AGRHYMET, INRAB-Benin, IRAG-Guinea, INRAN-Niger and ITRA-Togo. The project aimed at strengthening the capacity of the stakeholders of four WAAPP implementing countries to mainstream and implement Climate Smart Agriculture (CSA) into their activities.